1972
DOI: 10.1111/j.1600-0404.1972.tb07561.x
|View full text |Cite
|
Sign up to set email alerts
|

FIBRINOLYSIS AND SUBARACHNOID HAEMORRHAGE. INHIBITORY EFFECT OF TRANEXAMIC ACIDA Clinical Study

Abstract: In 4 patients with subarachnoid haemorrhage after ruptured intracranial aneurysm, tranexamic acid (AMCA) was used to prevent the recurrence of the bleeding. 1000 mg of AMCA was given intravenously 6 times a day for 8 days. The fibrinolytic activity of blood and spinal fluid was measured simultaneously with the etermination of AMCA levels before and after the beginning of treatment. The fibrin plate method showed no fibrinolytic activity in plasma or in CSF. Local fibriolysis was demonstrated by the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…1 In the past, several studies investigating plasma fibrinolytic activity in patients with SAH did not demonstrate an increase in plasma fibrinolytic activity. [2][3][4] However, in contrast to the results of these older studies, we observed in our study an unexplained 3-week increase in plasma fibrinolytic activity in placebo-treated patients.…”
contrasting
confidence: 57%
“…1 In the past, several studies investigating plasma fibrinolytic activity in patients with SAH did not demonstrate an increase in plasma fibrinolytic activity. [2][3][4] However, in contrast to the results of these older studies, we observed in our study an unexplained 3-week increase in plasma fibrinolytic activity in placebo-treated patients.…”
contrasting
confidence: 57%
“…These gastrointes tinal symptoms were reported in relation to the oral route of administration, however, Fodstad et al (5) reported similar incidence of nausea and vomiting by administering 1 g AMCA i.v. Tovi et al (21) observed that such nausea was obviated by prolongating the injection time to 5-10 min. The causes of such nausea and vomiting have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent the recurrent hemorrhage from aneurysm, accumulation of the antifibrinolytics in cerebrospinal fluid (CSF) is reported es sential (21). If so, this will turn out to be prolonged clot lysis in CSF spaces, then to be increased incidence of hydrocephalus.…”
Section: Sengupta Et At (19) Mullan and Dawleymentioning
confidence: 99%
See 1 more Smart Citation
“…Both drugs are readily absorbed from the gastrointestinal tract, penetrating the blood-brain barrier and entering the CSF. 31 - 32 The drugs have a short half-life, ranging from 1 to 3 hours. 23 - 3334 The daily dose of EACA, which is the most commonly used drug in the United States, is 24-36 g; that of tranexamic acid, which is most popular in Europe, is around 6 g (4-12 g).…”
mentioning
confidence: 99%